A 1860MPa grade hot-rolled multiphase wire rod for bridge cables and a manufacturing method thereof
Through the design of C-SI-Mn-CR chemical ingredients and the micro-quenching of online salt, the existing hot-rolled phase bars in terms of strength and plasticity have been solved, and the efficient manufacturing of 1860MPA bridge cables is realized, reducing The mechanical performance fluctuations and improved the strong plasticity of the organization.
Patent Information
- Application Number
- CN202411536306.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing hot-rolled composite phase strips for 1860MPa-level bridge cables have shortcomings in terms of strength and plasticity, especially in terms of mechanical properties fluctuations and tissue control difficulty of small-sized strips.
Through C-Si-Mn-Cr chemical composition design combined with online molten salt micro-quenching isothermal technology, the wire rod is controlled to quickly enter the mixed phase zone of bainite and sorbite from the high-temperature austenite state, forming a mainly fine lamellar spacing. A mixed structure composed of sorbite and a small amount of bainite, and isothermal tempering is performed to improve the strong plasticity matching of the wire rod.
It can effectively control the wire rod multi-phase structure, improve the network carbide problem, avoid abnormal martensite structure, reduce mechanical property fluctuations, improve tensile strength and area shrinkage, and is suitable for the manufacture of 1860MPa bridge cables.
Smart Images

Figure CN119040752B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods, and in particular relates to a hot-rolled multiphase wire rod for 1860MPa-grade bridge cables and a manufacturing method thereof. Background Art
[0002] At present, the steel wire for bridge cables is generally made of hypereutectoid hot-rolled wire rods through drawing and galvanizing. Therefore, the hot-rolled wire rod base material determines the strength grade of the bridge cable. As bridges gradually develop into large-span suspension or cable-stayed bridges, the performance requirements of bridge cables are constantly improving, and the torsion index is strict. Therefore, further requirements are put forward for the strength grade and toughness of hot-rolled wire rods for bridge cables. The existing 1860MPa grade hot-rolled complex phase wire rod products for bridge cables usually strengthen the original strength of the wire rod by adding trace alloy elements such as Si, Mn, Cr, and V. For example, patent CN112501506B discloses a steel wire rod for bridge cables and its manufacturing method. The phase transformation is controlled by the Stelmor air-cooling line, and the microstructure and performance of the wire rod are regulated to be a high-content fine pearlite, i.e., a troostite structure. However, there are still the following technical difficulties in manufacturing hot-rolled wire rods with better strength and plasticity that can meet the downstream wire making and torsion performance requirements:
[0003] 1. As strengthening elements, C and Mn can improve the strength of materials through solid solution strengthening, but a large amount of addition will also aggravate the component segregation during the solidification process of the alloy. During the Stelmor air cooling process, due to the limited maximum cooling rate of air cooling, which can only reach about 10℃ / s at most, and in order to make the wire rod obtain the sorbite structure with good drawing performance in the pearlite phase region, the cooling temperature gradient after wire drawing is limited, so that the wire rod passes through the secondary cementite precipitation temperature range of 700~800℃ for a long time after wire drawing. Affected by segregation, the excessively high concentration of carbon precipitates in the form of carbides along the austenite grain boundaries to form network carbides, destroying the continuity of the organization, reducing the toughness of the wire rod, increasing its brittleness, and easily failing due to fatigue during use; and reducing the C and Mn content will bring about a large strength loss. When the wire rod specification is small, it is necessary to increase the content of precious alloys such as V, which will increase the material cost and the strength improvement is limited.
[0004] 2. The addition of Mn and Cr components increases the hardenability, so that the wire rod can more easily obtain more and finer cementite lamellae at a lower phase transition temperature under air cooling conditions. In order to minimize the adverse effects of network carbides, the fan air volume will be increased and the cooling process will be accelerated after spinning. However, the distribution and uncontrollability of air volume and air temperature will increase, and the temperature difference between the windward side and the leeward side of the wire rod will increase. Affected by segregation and hardenability, some wire rods that are cooled too quickly are more likely to form brittle bainite or martensite abnormal structures, which will obviously affect the plasticity of the structure and increase the fluctuation of the mechanical properties of the wire rod. It is difficult to effectively control the structure and performance of the wire rod, resulting in unqualified performance such as broken wire and torsion in the downstream wire making process. Reducing the Mn and Cr content or the air cooling intensity will lose the strengthening effect. At the same time, the phase transition temperature will rise, and the pearlite content with larger interlamellar spacing will increase, which will bring about a large strength loss.
[0005] 3. The addition of Cr increases the strength of cementite, but also increases the difficulty of microstructure control and plasticity improvement. In order to increase the troostite content in high carbon steel wire rod, the air cooling line will reduce the air cooling intensity to prolong the phase transformation time after approaching the pearlite phase transformation temperature range, but the minimum cooling rate of wire rod air cooling can only reach about 3°C / s. Even if insulation or delayed cooling is adopted, the wire rod is still in continuous cooling. Due to insufficient supercooling, the cementite lamellae obtained by phase transformation are coarse, and elements such as Mn affect the diffusion activity of carbon. After continuous cooling phase transformation, the wire rod temperature is too low and the thermal driving force is insufficient, which will increase the difficulty of wire rod softening. Although the obtained high troostite content wire rod has high strength, the plasticity is insufficient. Increasing the soft phase ferrite content in the microstructure will significantly reduce the strength of the wire rod, resulting in wire rod breakage during wire making or torsion, or it is difficult to reach the performance level of 1860MPa bridge cable. Summary of the invention
[0006] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a hot-rolled multiphase wire rod for 1860MPa bridge cables and a manufacturing method thereof, which can improve the strength and plasticity of the wire rod by regulating the multiphase structure and reduce the fluctuation of the mechanical properties of small-sized wire rods. It is used to manufacture 1860MPa bridge cables, which is beneficial to improving the current situation of unqualified performance such as wire breakage and torsion in the downstream wire making process.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] A method for manufacturing a 1860MPa grade hot-rolled multiphase wire rod for bridge cables, the manufacturing method comprising:
[0009] The wire rod is produced by rolling according to the chemical composition of the hot-rolled complex phase wire rod, and the chemical composition and mass percentage of the hot-rolled complex phase wire rod include: C: 0.81%~0.85%, Si: 0.15%~0.28%, Mn: 0.46%~0.75%, Cr: 0.45%~0.55%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into a wire rod at a spinning temperature of ≥880°C, and then subjected to online molten salt micro-quenching isothermal treatment , so that the wire rod is cooled at a cooling rate of ≥39℃ / s, and enters the mixed phase region of bainite and troostite from the austenite state, so that most of the austenite transforms into troostite and a small part of the austenite transforms into bainite, and isothermal tempering is performed to promote the melting of the troostite lamellar layer. Finally, it is slowly cooled by a roller to obtain a hot-rolled complex phase wire rod with a microstructure including 76%~83% tempered troostite by volume, 11%~18% tempered bainite by volume, and the rest being a complex phase structure composed of ferrite and fused troostite.
[0010] The chemical composition and mass percentage design basis of the hot rolled multiphase wire rod include:
[0011] (1) Carbon: Carbon is the main strengthening element in steel and has a significant effect on the strength and plasticity of bridge cable steel. As the carbon content increases, it is conducive to the formation of more cementite lamellae and refined troostite lamellae structure, which improves the tensile strength of the matrix and is conducive to improving the strength of the steel wire through work hardening during the subsequent wire drawing process. However, if the carbon content is too high, it will make it more difficult to control the central segregation, decarburization and network carbides of the high-carbon steel alloy billet. Therefore, in order to take into account the high strength and toughness requirements of the 1860MPa grade bridge cable and reduce the difficulty of controlling the uniformity of the structure, it is chosen to appropriately reduce the carbon content, reduce the influence of segregation, and be more conducive to obtaining a mixed structure of troostite and bainite during the online molten salt micro-quenching isothermal treatment. The mass percentage of C is controlled to be 0.81%~0.85%.
[0012] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. It has a strong solid solution strengthening ability, which is beneficial to obtaining a finer troostite structure. At the same time, it can inhibit the coarsening of cementite and accelerate the diffusion rate of carbon, which is beneficial to promoting the formation of bainite and troostite melting, and reducing the strength loss in the subsequent hot-dip galvanizing process. However, excessive silicon will promote C desolvation and prolong the phase transformation time, which is not conducive to the rapid phase transformation and tempering in the online molten salt micro-quenching isothermal process, affecting the plasticity of the wire rod. Therefore, the Si content is appropriately reduced, and the mass percentage of Si is controlled to be 0.15%~0.28%.
[0013] (3) Manganese: Mn can be added as a deoxidizer in the steelmaking process. As a strengthening element, it mainly plays a role in solid solution strengthening. At the same time, it improves the hardenability of the wire rod, reduces the phase transformation temperature, and makes it easier to obtain finer bainite and bainite structures to improve the matrix strength. However, when the Mn content is too high, it will increase the central alloy element segregation of the steel billet, increase the grain coarsening tendency of the material during the heating process and the risk of precipitation of low-temperature martensite structure, and reduce the diffusion activity of carbon. It is not conducive to promoting the rapid melting of bainite and the tempering softening of the mixed structure during online molten salt micro-quenching isothermal, thereby reducing the plasticity of the wire rod. Therefore, in order to take into account the high strength and plasticity of the hot-rolled wire rod and reduce the difficulty of controlling the uniformity of the structure, the mass percentage of Mn is controlled to be 0.46%~0.75%.
[0014] (4) Chromium: As a medium-strong carbide-forming element, Cr can improve the stability of austenite and the hardenability of wire rod, prevent the growth of grains during rolling, and refine the spacing between troostite lamellae at the same cooling rate, improve the strength of cementite, promote bainite nucleation, further improve the strength of wire rod and the work hardening rate during wire drawing, and reduce the strength loss during the subsequent hot-dip galvanizing of steel wire. However, high Cr content will aggravate segregation, increase the risk of abnormal martensite organization precipitation, increase the difficulty of improving plasticity, and affect the torsional performance of steel wire. Therefore, the Cr content is appropriately increased, and the mass percentage of Cr is controlled to be 0.45%~0.55%.
[0015] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0016] The hot-rolled complex phase wire rod adopts C-Si-Mn-Cr composition design, does not contain V, Ni and other components, and appropriately reduces the C content, reduces the difficulty and influence of segregation control, optimizes the C, Si, Mn, Cr ratio, and regulates the peak precipitation temperature of sorbite and bainite structures to be close, which provides favorable conditions for promoting the formation and tempering of complex phase structures in online molten salt micro-quenching. On this basis, the appropriate wire-spinning temperature is selected to austenitize the wire rod, avoid the precipitation of network carbides in the wire-spinning stage, and then directly carry out online molten salt micro-quenching isothermal treatment:
[0017] 1. Compared with the Stelmor air-cooled line, which has a limited maximum cooling capacity and a high phase transformation control temperature, the above-mentioned manufacturing method utilizes the high heat exchange capacity of molten salt and the mixed phase region of bainite and troostite with a lower temperature than the pearlite phase region, so that the wire rod can be quickly cooled from the high-temperature austenite state after spinning. On the one hand, it effectively reduces the time for the wire rod to pass through the precipitation temperature range of secondary cementite and tertiary cementite, improves the adverse effect of segregation on the control of network carbides caused by the high C content of hypereutectoid steel, avoids the precipitation of network cementite along the grain boundary and the sharp decrease in the plastic toughness of the material, and improves the strengthening effect of carbon element. On the other hand, compared with cooling to the pearlite phase transformation range, the temperature gradient of the spinning temperature dropping to the mixed phase region is larger, and a larger degree of supercooling can be formed after rapid cooling, which promotes the rapid nucleation of troostite and bainite with finer interlamellar spacing, improves the phase transformation rate and matrix strength, and provides favorable conditions for rapid isothermal tempering.
[0018] 2. Compared with Stelmore air-cooled wire controlled cooling, which has large fluctuations and is difficult to effectively control abnormal structures, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for more uniform and rapid heat exchange, and there is no problem of the windward side and the leeward side. It can effectively reduce the temperature difference in the same circle of small-sized wire rods, and avoid the wire rods being affected by hardenability and segregation to produce abnormal martensitic structures that are unfavorable to drawing properties and plasticity. At the same time, by making the wire rod temperature consistent with the molten salt temperature, it is in the mixed phase region of bainite and troostite for a longer period of phase transformation, which can make the high-temperature austenite phase transformation form a mixed structure composed of troostite and a small amount of bainite with fine lamellar spacing as the main component, making the bainite phase transformation that is conventionally regarded as an abnormal structure more controllable and uniform, thereby improving the uniformity of the structure, reducing the fluctuation of mechanical properties, and further improving the matrix strength through a small amount of bainite, making up for the strength loss caused by not adding elements such as V and Ni and reducing the C content. At the same time, compared with the salt bath treatment in the pearlite phase region and the bainite phase region respectively, the above-mentioned online molten salt micro-quenching isothermal can simplify the process and is conducive to improving production capacity.
[0019] 3. Compared with the limited minimum cooling capacity and continuous cooling of the Stelmore air-cooled line, which leads to low plasticity of the wire rod, the wire rod can be maintained in the mixed phase area of bainite and troostite for a longer period of tissue incubation and isothermal tempering when it undergoes online molten salt micro-quenching. On the basis of finer spacing between troostite lamellae and reduced tempering difficulty, the wire rod is isothermally treated at a higher temperature instead of continuously cooled to provide more thermal power, which promotes the formation of a mixed structure of troostite and bainite, can reduce the proportion of ferrite, improve matrix strength, and promote the melting and tempering of troostite lamellae. Tempering transforms it into tempered bainite and fused bainite, reduces organizational stress and dislocation density, improves plasticity, and enables the hard and brittle bainite to retain strength characteristics and reduce dislocation density after being transformed into tempered bainite through tempering, so as to obtain a strong and tough organizational state, compensate for the adverse effect of increasing Cr content on the plasticity of wire rod, and effectively utilize the bainite organization that is conventionally regarded as an abnormal organization. In the further roller slow cooling treatment, the higher temperature state of the wire rod after leaving the molten salt can be continued, and further tempering and softening can be achieved through slow cooling, thereby regulating the complex phase organization and improving the strength-plasticity matching of the wire rod.
[0020] Before the rolling, an appropriate heating furnace temperature is selected to promote uniform diffusion of alloy components and avoid excessively high soaking temperature and decarburization caused by high carbon content during the furnace time. In a preferred embodiment, before the rolling, the soaking temperature of the heating furnace is controlled to be 1110~1150℃ and the furnace time is 150~300min.
[0021] Due to the high spinning temperature, a higher initial rolling temperature and reduction can be selected during rolling to promote rapid rolling deformation of the steel billet, improve rolling efficiency and avoid grain growth. In a preferred embodiment, during rolling, the initial rolling temperature is controlled to be 1080~1120℃, and the initial rolling reduction is 25%~30%.
[0022] During the rolling, a suitable rolling temperature and deformation amount are selected to promote dynamic recrystallization during the final rolling process, refine the grains, and strengthen the matrix. In a preferred embodiment, during the rolling, the final rolling temperature is controlled to be 900~930℃, and the final rolling reduction is 27%~33%.
[0023] In a preferred embodiment, the molten salt temperature of the online molten salt micro-quenching isothermal treatment is 435~475℃, and the treatment time is 50~125s. This temperature is in the mixed phase region of bainite and troostite of the hot-rolled complex phase wire rod. The lower the molten salt temperature, the more beneficial it is to form a troostite structure with finer interlamellar spacing and a bainite structure with a larger proportion, thereby improving the matrix strength. However, if the molten salt temperature is too low, the bainite transformation is too much, and it cannot provide more thermal power for isothermal tempering, which will lead to a decrease in the softening effect of isothermal tempering and insufficient plasticity of the wire rod. On the contrary, the higher the molten salt temperature, the less bainite phase transformation, and the mixed structure of troostite and bainite can soften quickly, which is beneficial to the melting of the troostite lamellae and increases the plasticity of the wire rod. However, if the molten salt temperature is too high, the interlamellar spacing of the troostite becomes coarser, and even the bainite structure cannot be formed, which will Leading to insufficient strength of wire rod; the longer the treatment time, the more complete the phase transformation, the lower the proportion of ferrite, and the better the isothermal tempering softening effect, which can increase the plasticity of wire rod, but if the treatment time is too long, there will be a risk of over-softening or loss of strength and plasticity due to precipitation and coarsening of Cr, which is not conducive to efficient production; on the contrary, the shorter the treatment time, the lower the isothermal tempering softening effect and the plasticity of wire rod, but if the treatment time is too short, the wire rod is not softened, which will bring greater brittleness, and even insufficient phase transformation, reduced troostite proportion, increased ferrite, and even in the subsequent cooling due to residual martensite abnormal organization, resulting in loss of strength and plasticity and increased fluctuation of mechanical properties. Therefore, the molten salt temperature and treatment time can be further controlled to regulate the phase transformation and isothermal tempering state of the mixed organization, so as to regulate the complex phase organization and strength and plasticity of wire rod.
[0024] In a preferred embodiment, the online molten salt micro-quenching isothermal treatment is divided into a front-stage treatment and a back-stage treatment. The molten salt circulation volume of the front-stage treatment is greater than that of the back-stage treatment. The processing time of the front-stage treatment is 10-25s, and the processing time of the back-stage treatment is 30-100s. The temperature difference of the wire rod from the spinning temperature to the mixed phase zone temperature is large. The front-stage treatment uses a larger molten salt circulation volume, which can promote the wire rod to quickly skip the network carbide precipitation interval from the high-temperature austenite state and enter the mixed phase zone to form troostite with fine lamellar spacing as the main component and a small amount of bainite. After that, the difficulty of controlling the molten salt temperature rise is reduced. The back-stage treatment uses a smaller molten salt circulation volume, which can accurately control the temperature, promote the isothermal tempering of the mixed structure of troostite and bainite, and the melting of the troostite lamellar layers. At the same time, the reduced molten salt circulation volume can reduce production energy consumption and costs.
[0025] In a preferred embodiment, the molten salt circulation rate of the front-stage treatment is 660-820 t / h, and the molten salt temperature rise is ≤8°C.
[0026] In a preferred embodiment, the molten salt circulation rate of the post-processing is 260-360 t / h, and the molten salt temperature rise is ≤4°C.
[0027] In a preferred embodiment, the roller slow cooling controls the wire rod to be cooled to below 320°C at a slow cooling rate of 0.10-0.25°C / s for coiling. Selecting a lower slow cooling rate can promote further tempering, improve the softening effect, and avoid loss of wire rod plasticity due to excessive cooling.
[0028] In a preferred embodiment, the roller slow cooling utilizes the hot air from the online molten salt micro-quenching isothermal treatment to control the cooling of the wire rod, and utilizes the hot air radiation to further reduce the wire rod slow cooling speed of the roller slow cooling, so as to recycle the production heat energy and reduce the production energy consumption. At the same time, in order to increase the roller speed, it is avoided that the wire rod accumulation and the impact on the processing efficiency are caused by relying solely on the wire rod's own heat energy to control cooling.
[0029] In a preferred embodiment, the roller slow cooling is closed by a heat preservation cover, and the hot air of the online molten salt micro-quenching isothermal treatment is blown to the conveying roller, and the wire rod is conveyed by the conveying roller into the heat preservation cover, which can further utilize the hot air radiation and reduce the waste of heat energy.
[0030] A 1860MPa grade hot-rolled complex phase wire rod for bridge cables, wherein the hot-rolled complex phase wire rod is manufactured by any one of the above-mentioned methods for manufacturing the 1860MPa grade hot-rolled complex phase wire rod for bridge cables.
[0031] The hot-rolled multiphase wire rod adopts the C-Si-Mn-Cr hypereutectoid chemical composition design without V, Ni and other elements, and the C, Si and Mn contents are relatively low. At the same time, compared with the traditional stranded wire rod structure of pearlite / sodium + ferrite, the microstructure of the hot-rolled multiphase wire rod includes mainly tempered bainite, containing a small amount of tempered bainite, ferrite and fused bainite. The interlamellar spacing of bainite is finer than that of pearlite, and the strength is higher. After tempering and lamellar melting are transformed into tempered bainite and fused bainite, the position The dislocation density decreases and the plasticity is further improved. The tempered bainite can retain the high strength characteristics of bainite. After tempering, the dislocation density decreases and becomes strong and tough, which can reduce the proportion of ferrite and does not contain abnormal martensite structure. The proportion of tempered bainite is more controllable, which can make up for the strength loss caused by reducing the C or Si or Mn content, and further improve the strength of the wire rod. At the same time, the overall plasticity and toughness properties are improved by regulating the tempering state, and the adverse effects of increasing the Cr content on plasticity are improved, thereby achieving high strength and plasticity matching of the wire rod.
[0032] The finer the tempered bainite lamellae spacing, the greater the proportion of tempered bainite and the higher the wire rod strength as the molten salt temperature decreases. However, if the tempered bainite lamellae spacing is too fine, the molten salt temperature becomes low, which is not conducive to rapid isothermal tempering for efficient production. In a preferred embodiment, the tempered bainite lamellae spacing is 65~100nm.
[0033] In a preferred embodiment, the network carbide level of the hot-rolled multiphase wire rod is level 0, which can avoid the adverse effects of the network carbide on the uniformity and plasticity of the structure and improve the drawing performance of the wire rod.
[0034] The wire rod network carbide level is lower and does not contain abnormal structures such as martensite, the uniformity of the structure is improved, and the fluctuation of mechanical properties is smaller. In a preferred embodiment, the mechanical property difference of the hot-rolled complex phase wire rod is ≤38MPa, which can reduce the risk of wire breakage.
[0035] In a preferred embodiment, the diameter of the hot-rolled complex phase wire rod is 7.0~13.0mm, the tensile strength is 1310~1360MPa, and the cross-sectional shrinkage rate is 40%~45%. The diameter specification of the hot-rolled wire rod is small, which is conducive to quickly reaching the target diameter of the bridge cable steel wire, thereby reducing the number of drawing passes and improving processing efficiency. The wire rod has higher tensile strength and better cross-sectional shrinkage rate, can quickly reach the target strength, avoid excessive loss of wire rod plasticity during wire rod drawing and cause wire breakage, and reduce the risk of torsion breakage.
[0036] Compared with the prior art, the beneficial effects of the present invention are at least:
[0037] (1) In view of the current situation that the existing Stelmor air-cooled line has large fluctuations in controlled cooling, it is difficult to effectively control the microstructure and performance of the wire rod, resulting in unqualified performance such as wire breakage and torsion in the downstream wire-making process, the manufacturing method of the present invention, through the C-Si-Mn-Cr chemical composition design combined with the online molten salt micro-quenching isothermal technology, can control the wire rod to quickly skip the network carbide precipitation zone from the high-temperature austenite state and enter the bainite and troostite mixed phase zone, forming a mixed structure composed of troostite with fine lamellar spacing as the main component and a small amount of bainite, and isothermal tempering is performed at the same time to improve the strength and plasticity matching of the wire rod, and finally the wire rod is slowly cooled by rollers to promote further slow cooling and tempering, thereby improving the softening effect of the wire rod, and can effectively control the complex phase structure of the wire rod, effectively improve the network carbide problem, avoid the abnormal martensite structure, and reduce the fluctuation of the mechanical properties of the wire rod. It is suitable for the manufacture of small-sized wire rods and can be produced efficiently, and has good industrial adaptability.
[0038] (2) In view of the current situation that the existing pearlite / bainite + ferrite stranded steel wire rod has insufficient strength and plasticity or large fluctuations in mechanical properties, the microstructure of the hot-rolled multiphase wire rod of the present invention includes mainly tempered bainite, containing a small amount of tempered bainite, ferrite and melt bainite. By utilizing the refinement of bainite lamellae and melt tempering, and the controllable phase transformation and tempering toughening of bainite, the high-strength characteristics can be retained, and the strength loss caused by reducing the C, Si or Mn content can be compensated, and the strength of the wire rod can be further improved. At the same time, the overall plasticity and toughness can be improved by regulating the tempering state, and the adverse effect of increasing the Cr content on plasticity can be improved. The tensile strength can reach 1310~1360MPa and the cross-sectional shrinkage rate can reach 40%~45%. The wire rod microstructure and performance can be effectively controlled, and it can be used in the manufacture of 1860MPa-level bridge cables and other application fields. It can reduce the risk of wire breakage in the downstream wire making process, meet the torsional performance requirements, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0040] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0041] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0042] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0043] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0044] A preferred embodiment of the manufacturing method of the 1860MPa grade hot-rolled multiphase wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.81%, Si: 0.26%, Mn: 0.55%, Cr: 0.52%, P: 0.012%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:
[0045] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire with a diameter of 11mm through a rolling line after the steel billet leaves the heating furnace. Select appropriate rolling temperature and reduction amount to promote rapid rolling deformation of the steel billet, and control dynamic recrystallization and grain refinement during the final rolling process. Specifically: control the heating furnace soaking temperature to 1150 ℃, the furnace time is 150min, the initial rolling temperature is 1120℃, the initial rolling reduction is 26%, the final rolling temperature is 930℃, and the final rolling reduction is 29%; the wire-spinning process is used to convert the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The appropriate wire-spinning temperature is selected to austenitize the wire rods, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent nucleation of sorbite and bainite. Specifically: the wire-spinning temperature is controlled to be 905℃.
[0046] The online molten salt micro-quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to enter the bainite and troostite mixed phase area, inhibiting the formation of network carbides, so that most of the austenite is transformed into troostite, and a small part of the austenite is transformed into bainite. The troostite structure is mainly composed of fine lamellar spacing, and then conveyed by a roller. It is sent through the second salt bath for post-processing, reducing the molten salt circulation volume, controlling phase change and performing isothermal tempering at the same time, promoting the melting of the sorbite lamellar layer, and improving the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 475°C, and the total processing time is 86s, of which the processing time of the front-stage treatment is 10s, the molten salt circulation volume is 720t / h, and the molten salt temperature rise is ≤8°C; the processing time of the back-stage treatment is 76s, the molten salt circulation volume is 320t / h, and the molten salt temperature rise is ≤4°C.
[0047] The roller slow cooling process is closed by a heat preservation cover, and the hot air above the two salt bath tanks of the online molten salt micro-quenching isothermal treatment is blown to the conveying roller, and the wire rod is conveyed by the conveying roller into the heat preservation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 300°C at a slow cooling rate of 0.25°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 As shown, the microstructure includes 83% tempered bainite by volume, 11% tempered bainite by volume, 4% ferrite by volume and 2% fused bainite by volume. The interlamellar spacing of the tempered bainite is 100nm, the network carbide grade is 0, the mechanical property difference is 37MPa, the tensile strength is 1310MPa, and the section reduction rate is 45%.
[0048] Comparative Example 1:
[0049] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1140°C, the furnace time is 180min, the initial rolling temperature is 1110°C, the final rolling temperature is 925°C, and the spinning temperature is 900°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~6# fans at 65%, cool the wire rod to 645℃ at a cooling rate of 6.8℃ / s, and then open 7~14# fans at 30%, cool the wire rod to 295℃ at a cooling rate of 3.2℃ / s. The hot-rolled wire rod is obtained after it comes off the line. The microstructure includes 80% tempered bainite and 20% ferrite by volume, the network carbide grade is 2.5, the mechanical property difference is 78MPa, the tensile strength is 1150MPa, and the section shrinkage is 37%.
[0050] From the comparison results of Example 1 and Comparative Example 1, it can be seen that after reducing the C and Mn contents, the Stelmor air cooling line process is adopted. Since the cooling rate is uncontrollable during the cooling phase transformation process, the strengthening effect is weakened, and network carbide carbon will still be generated due to the C element, it is difficult to effectively control the wire rod microstructure performance, the ferrite accounts for a high proportion, and the hot-rolled wire rod has insufficient strength and plasticity, especially the strength is poor. The present invention is combined with the online molten salt micro-quenching isothermal technology to control the wire rod to quickly skip the network carbide precipitation interval from the high-temperature austenite state and enter the bainite and troostite mixed phase area, forming a mixed structure composed of troostite mainly with fine lamellar spacing and a small amount of bainite, and isothermal tempering is performed at the same time to improve the strength and plasticity matching of the wire rod, avoid abnormal martensite structure, and reduce the fluctuation of the mechanical properties of the wire rod.
[0051] Comparative Example 2:
[0052] A method for manufacturing a hot-rolled complex phase wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1080°C, the furnace time is 250min, the initial rolling temperature is 1030°C, the final rolling temperature is 870°C, and the spinning temperature is 840°C. During the front stage of the online molten salt micro-quenching isothermal process, the wire rod is cooled at a cooling rate of 32°C / s, and a hot-rolled complex phase wire rod finished product is obtained after it comes off the line. Embodiment 2:
[0053] A preferred embodiment of the manufacturing method of the 1860MPa grade hot-rolled multiphase wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.81%, Si: 0.19%, Mn: 0.75%, Cr: 0.55%, P: 0.015%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:
[0054] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire with a diameter of 13mm through a rolling line after the steel billet leaves the heating furnace. Select appropriate rolling temperature and reduction amount to promote rapid rolling deformation of the steel billet, and control dynamic recrystallization and grain refinement during the final rolling process. Specifically: control the heating furnace soaking temperature to 1135 ℃, the furnace time is 250min, the initial rolling temperature is 1110℃, the initial rolling reduction is 25%, the final rolling temperature is 920℃, and the final rolling reduction is 27%; the wire-spinning process is used to convert the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The appropriate wire-spinning temperature is selected to austenitize the wire rods, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent nucleation of sorbite and bainite. Specifically: the wire-spinning temperature is controlled to be 895℃.
[0055] The online molten salt micro-quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to enter the bainite and troostite mixed phase area, inhibiting the formation of network carbides, so that most of the austenite is transformed into troostite, and a small part of the austenite is transformed into bainite. The troostite structure is mainly composed of fine lamellar spacing, and then conveyed by a roller. The wire rod is passed through the second salt bath for the post-processing, the molten salt circulation volume is reduced, the phase change is controlled and isothermal tempering is performed simultaneously, the melting of the sorbite lamellar layer is promoted, and the strength-plasticity matching of the wire rod is improved. Specifically: the molten salt temperature is 448°C, and the total processing time is 125s, of which the processing time of the front-stage processing is 25s, the molten salt circulation volume is 785t / h, and the molten salt temperature rise is ≤8°C; the processing time of the back-stage processing is 100s, the molten salt circulation volume is 260t / h, and the molten salt temperature rise is ≤4°C.
[0056] The roller slow cooling process is closed by a heat preservation cover, and the hot air above the two salt bath tanks of the online molten salt micro-quenching isothermal treatment is blown to the conveying roller, and the wire rod is conveyed by the conveying roller into the heat preservation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 310°C at a slow cooling rate of 0.15°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0057] Comparative Example 3:
[0058] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which differs from that of Example 2 in that: during the front-end treatment of the online molten salt micro-quenching isothermal process, the wire rod is cooled at a cooling rate of 36°C / s, the molten salt temperature is 500°C, and a hot-rolled complex phase wire rod finished product is obtained after it comes off the line.
[0059] Comparative Example 4:
[0060] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which differs from that of Example 2 in that: during the front-end treatment of the online molten salt micro-quenching isothermal process, the wire rod is cooled at a cooling rate of 42°C / s, the molten salt temperature is 425°C, and a hot-rolled complex phase wire rod finished product is obtained after it comes off the line. Embodiment 3:
[0061] A preferred embodiment of the method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.83%, Si: 0.15%, Mn: 0.63%, Cr: 0.45%, P: 0.012%, S: 0.013%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:
[0062] The rolling process is used to heat the steel billet with a specification of 180mm×180mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire with a diameter of 7mm through a rolling line after the steel billet leaves the heating furnace. Select appropriate rolling temperature and reduction amount to promote rapid rolling deformation of the steel billet, and control dynamic recrystallization and grain refinement during the final rolling process. Specifically: control the heating furnace soaking temperature to 1125 ℃, the furnace time is 300min, the initial rolling temperature is 1095℃, the initial rolling reduction is 30%, the final rolling temperature is 910℃, and the final rolling reduction is 33%; the wire-spinning process is used to make the wire rods out of the rolling line through the wire-spinning mechanism into wire rods, the wire rods are spread on the rollers and transported along the rollers, and the appropriate wire-spinning temperature is selected to austenitize the wire rods, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent nucleation of sorbite and bainite. Specifically: the wire-spinning temperature is controlled to be 885℃.
[0063] The online molten salt micro-quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to enter the bainite and troostite mixed phase area, inhibiting the formation of network carbides, so that most of the austenite is transformed into troostite, and a small part of the austenite is transformed into bainite. The troostite structure is mainly composed of fine lamellar spacing, and then conveyed by a roller. It is sent through the second salt bath for post-processing, reducing the molten salt circulation volume, controlling phase change and performing isothermal tempering at the same time, promoting the melting of the sorbite lamellar layer, and improving the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 461°C, and the total processing time is 112s, of which the processing time of the front-stage processing is 17s, the molten salt circulation volume is 660t / h, and the molten salt temperature rise is ≤8°C; the processing time of the back-stage processing is 85s, the molten salt circulation volume is 300t / h, and the molten salt temperature rise is ≤4°C.
[0064] The roller slow cooling process is closed by a heat preservation cover, and the hot air above the two salt bath tanks of the online molten salt micro-quenching isothermal treatment is blown to the conveying roller, and the wire rod is conveyed by the conveying roller into the heat preservation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 305°C at a slow cooling rate of 0.2°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0065] Comparative Example 5:
[0066] A method for manufacturing a hot-rolled complex phase wire rod, which differs from Example 3 in that the total online molten salt micro-quenching isothermal treatment time is 45 seconds, of which the treatment time of the front-end treatment is 17 seconds and the treatment time of the back-end treatment is 28 seconds, and a hot-rolled complex phase wire rod finished product is obtained after going offline.
[0067] Comparative Example 6:
[0068] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which differs from Example 3 in that the total online molten salt micro-quenching isothermal treatment time is 150 s, of which the treatment time of the front-end treatment is 17 s, and the treatment time of the back-end treatment is 133 s, and a hot-rolled complex phase wire rod finished product is obtained after going offline. Embodiment 4:
[0069] A preferred embodiment of the method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.85%, Si: 0.28%, Mn: 0.46%, Cr: 0.48%, P: 0.013%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → roller slow cooling → coiling, specifically:
[0070] The rolling process is used to heat a steel billet with a specification of 180mm×180mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of alloy components and avoid decarburization, and roll the steel billet into a wire with a diameter of 9mm through a rolling line after the steel billet leaves the heating furnace. Select appropriate rolling temperature and reduction amount to promote rapid rolling deformation of the steel billet, and control dynamic recrystallization and grain refinement during the final rolling process. Specifically: control the heating furnace soaking temperature to 1110 ℃, the furnace time is 200min, the initial rolling temperature is 1080℃, the initial rolling reduction is 28%, the final rolling temperature is 900℃, and the final rolling reduction is 31%; the wire-spinning process is used to convert the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The appropriate wire-spinning temperature is selected to austenitize the wire rods, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent nucleation of sorbite and bainite. Specifically: the wire-spinning temperature is controlled to be 880℃.
[0071] The online molten salt micro-quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first salt bath tank for pre-treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to enter the bainite and troostite mixed phase area, inhibiting the formation of network carbides, so that most of the austenite is transformed into troostite, and a small part of the austenite is transformed into bainite. The troostite structure is mainly composed of fine lamellar spacing, and then conveyed by a roller. It is sent through the second salt bath for post-processing, reducing the molten salt circulation volume, controlling phase change and performing isothermal tempering at the same time, promoting the melting of the sorbite lamellar layer, and improving the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 435°C, and the total processing time is 50s, of which the processing time of the front-stage treatment is 20s, the molten salt circulation volume is 820t / h, and the molten salt temperature rise is ≤8°C; the processing time of the back-stage treatment is 30s, the molten salt circulation volume is 360t / h, and the molten salt temperature rise is ≤4°C.
[0072] The roller slow cooling process is closed with an insulation cover, and the hot air above the two salt bath tanks of the online molten salt micro-quenching isothermal treatment is blown to the conveying roller, and the wire rod is conveyed by the conveying roller into the insulation cover, so as to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 318°C at a slow cooling rate of 0.1°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage.
[0073] Comparative Example 7:
[0074] A method for manufacturing a hot-rolled complex phase wire rod, which differs from Example 4 in that: the method is manufactured according to the process flow of rolling → spinning → online molten salt micro-quenching isothermal → air cooling, and the air cooling process adopts opening the insulation cover to control the wire rod to be cooled to 285°C at a slow cooling rate of 1.2°C / s, and the hot-rolled complex phase wire rod finished product is obtained after it comes off the line.
[0075] The hot rolled multiphase wire rods obtained in the above examples 1 to 4 and comparative examples 2 to 7 were subjected to microstructure and performance tests, and the comparative results obtained are shown in Table 1 below:
[0076] Table 1. Comparison of microstructure and properties of hot rolled multiphase wire rods with different compositions and manufacturing methods
[0077]
[0078] It can be seen from the results of Examples 1 to 4 that the microstructure of the hot-rolled multiphase wire rod of the present invention is mainly composed of tempered bainite, a small amount of tempered bainite, ferrite and fused bainite, and can achieve a tensile strength of 1310 to 1360 MPa and a cross-sectional shrinkage rate of 40% to 45%. It can be used in the manufacture of 1860 MPa-level bridge cables and other application fields, can reduce the risk of wire breakage in the downstream wire-making process, and meet the torsional performance requirements.
[0079] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the appropriate spinning temperature is selected to austenitize the wire rod, avoid the precipitation of network carbides in the spinning stage, and provide favorable conditions for promoting the rapid formation of complex phase structure in online molten salt micro-quenching.
[0080] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the higher the molten salt temperature of the online molten salt micro-quenching isothermal treatment, the less the bainite phase transformation, the mixed structure of troostite and bainite can soften quickly, which is beneficial to the melting of troostite lamellae, and increases the plasticity of the wire rod. However, if the molten salt temperature is too high, the spacing between the tempered troostite lamellae is too coarse, the proportion of tempered bainite is too small, and the wire rod is too softened, which will lead to insufficient strength of the wire rod.
[0081] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the lower the molten salt temperature of the online molten salt micro-quenching isothermal treatment, the more beneficial it is to the formation of a troostite structure with finer interlamellar spacing and a bainite structure with a larger proportion, thereby improving the matrix strength. However, if the molten salt temperature is too low, the bainite transformation is too much, and more thermal power cannot be provided for isothermal tempering, the softening effect of isothermal tempering will be reduced and the plasticity of the wire rod will be insufficient.
[0082] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the shorter the treatment time of the online molten salt micro-quenching isothermal treatment, the lower the isothermal tempering softening effect and the plasticity of the wire rod. However, if the treatment time is too short and the wire rod is not softened, it will cause greater brittleness and increase the performance fluctuation of the wire rod.
[0083] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the longer the treatment time of the online molten salt micro-quenching isothermal treatment, the more complete the phase transformation, the lower the proportion of ferrite, and the better the isothermal tempering softening effect, which can increase the plasticity of the wire rod. However, if the treatment time is too long, there is a risk of excessive softening or loss of strength and plasticity due to the precipitation and coarsening of Cr, which is not conducive to efficient production.
[0084] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the selection of a lower slow cooling rate can promote further tempering of the wire rod, improve the softening effect, avoid the loss of wire rod plasticity due to too fast cooling, and can also recycle the production heat energy of the online molten salt micro-quenching isothermal treatment to reduce production energy consumption.
[0085] The series of detailed descriptions listed above are only specific descriptions of the feasible embodiments of the present invention, and they are not intended to limit the scope of protection of the present invention. For example, the steel billet is obtained by processing according to the converter smelting, refining, and continuous casting processes. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 1860MPa grade hot-rolled multiphase wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled multiphase wire rod, wherein the chemical composition and mass percentage of the hot-rolled multiphase wire rod include: C: 0.81%~0.85%, Si: 0.15%~0.28%, Mn: 0.46%~0.75%, Cr: 0.45%~0.55%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥880°C, it is subjected to an online molten salt micro-quenching isothermal treatment, so that the wire rod is cooled at a cooling rate of ≥39°C / s, and enters a mixed phase region of bainite and troostite from an austenite state, so that most of the wire rod is spun into a wire rod at a spinning temperature of ≥880°C. Austenite transforms into troostite, a small part of austenite transforms into bainite, and isothermal tempering is performed to promote the melting of troostite lamellae, and finally, it is slowly cooled by rollers to be made into a hot-rolled complex phase wire rod with a microstructure including 76% to 83% by volume of tempered troostite, 11% to 18% by volume of tempered bainite, and the rest being ferrite and fused troostite. The molten salt temperature of the online molten salt micro-quenching isothermal treatment is 435 to 475°C, the treatment time is 50 to 125s, and the roller slow cooling controls the wire rod to be cooled to below 320°C at a slow cooling rate of 0.10 to 0.25°C / s for coiling.
2. The method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1110-1150° C., and the time in the furnace is 150-300 minutes.
3. The method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1080-1120° C., the initial rolling reduction is 25%-30%, the final rolling temperature is controlled to be 900-930° C., and the final rolling reduction is controlled to be 27%-33%.
4. The method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to claim 1, characterized in that: The online molten salt micro-quenching isothermal treatment is divided into a front-end treatment and a back-end treatment. The molten salt circulation volume of the front-end treatment is 660-820 t / h, the molten salt temperature rise is ≤8°C, and the treatment time is 10-25s; the molten salt circulation volume of the back-end treatment is 260-360 t / h, the molten salt temperature rise is ≤4°C, and the treatment time is 30-100s.
5. The method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to claim 1, characterized in that: The roller slow cooling utilizes hot air from online molten salt micro-quenching isothermal treatment to control wire rod cooling.
6. A 1860MPa grade hot-rolled multiphase wire rod for bridge cables, characterized in that: The hot-rolled multiphase wire rod is manufactured by the method for manufacturing the 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to any one of claims 1 to 5.
7. The 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to claim 6, characterized in that: The interlamellar spacing of the tempered bainite is 65-100 nm, the network carbide level of the hot-rolled multiphase wire rod is level 0, and the mechanical property circle difference is ≤38 MPa.
8. The 1860MPa grade hot-rolled multiphase wire rod for bridge cables according to claim 6, characterized in that: The hot-rolled multiphase wire rod has a diameter of 7.0-13.0 mm, a tensile strength of 1310-1360 MPa, and a cross-sectional shrinkage of 40%-45%.
Citation Information
Patent Citations
14.9-grade annealing-free hot-rolled high-carbon cold heading steel wire rod and manufacturing method thereof
CN118621230A
Cold heading steel wire rod for 14.9-grade non-quenched and tempered bolt and manufacturing method of cold heading steel wire rod
CN118653095A